2006
DOI: 10.1104/pp.106.081091
|View full text |Cite
|
Sign up to set email alerts
|

Early Steps in the Biosynthesis of NAD in Arabidopsis Start with Aspartate and Occur in the Plastid

Abstract: NAD is a ubiquitous coenzyme involved in oxidation-reduction reactions and is synthesized by way of quinolinate. Animals and some bacteria synthesize quinolinate from tryptophan, whereas other bacteria synthesize quinolinate from aspartate (Asp) using l-Asp oxidase and quinolinate synthase. We show here that Arabidopsis (Arabidopsis thaliana) uses the Asp-to-quinolinate pathway. The Arabidopsis l-Asp oxidase or quinolinate synthase gene complemented the Escherichia coli mutant defective in the corresponding ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
167
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 28 publications
5
167
0
1
Order By: Relevance
“…In addition to the PMT and A622 transcripts, we found that transcripts encoding quinolinate synthase and two closely related transporters were considerably less abundant in the mutant roots. Tobacco quinolinate synthase is the second enzyme in the de novo NAD biosynthetic pathway, which provides the pyridine moiety of nicotine (Katoh et al, 2006). The two transporters NtMATE1 and NtMATE2 (collectively called NtMATE1/2) share 96.4% amino acid sequence identity with each other and belong to the multidrug and toxin extrusion (MATE) family (Fig.…”
Section: Molecular Cloning Of Ntmate1 and Ntmate2mentioning
confidence: 99%
“…In addition to the PMT and A622 transcripts, we found that transcripts encoding quinolinate synthase and two closely related transporters were considerably less abundant in the mutant roots. Tobacco quinolinate synthase is the second enzyme in the de novo NAD biosynthetic pathway, which provides the pyridine moiety of nicotine (Katoh et al, 2006). The two transporters NtMATE1 and NtMATE2 (collectively called NtMATE1/2) share 96.4% amino acid sequence identity with each other and belong to the multidrug and toxin extrusion (MATE) family (Fig.…”
Section: Molecular Cloning Of Ntmate1 and Ntmate2mentioning
confidence: 99%
“…Nicotine is composed of a pyridine ring and a pyrrolidine ring (see Supplemental Figure 1 online); ornithine decarboxylase (ODC; Imanishi et al, 1998), putrescine N-methyltransferase (PMT; Hibi et al, 1994), and N-methylputrescine oxidase (MPO; Heim et al, 2007;Katoh et al, 2007) are involved in the formation of the pyrrolidine ring, whereas the pyridine ring uses enzymes involved in the early steps of NAD biosynthesis, such as aspartate oxidase (AO), quinolinic acid synthase (QS), and quinolinic acid phosphoribosyl transferase (QPT) (Sinclair et al, 2000;Katoh et al, 2006). A PIP family oxidoreductase, A622, is also required for the biosynthesis of tobacco alkaloids, possibly to form a nicotinic acid-derived precursor (Deboer et al, 2009;Kajikawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Like other organisms, Arabidopsis (Arabidopsis thaliana) contains two NAD(P)(H) biosynthetic pathways: the de novo and salvage pathways (Katoh et al, 2006;Wang and Pichersky, 2007). In the salvage pathway, nicotinate mononucleotide (NaMN; an intermediate in the de novo pathway) is formed from nicotinamide (a product of NAD degradation) through two enzymatic steps (Katoh et al, 2006;Wang and Pichersky, 2007).…”
mentioning
confidence: 99%
“…In the salvage pathway, nicotinate mononucleotide (NaMN; an intermediate in the de novo pathway) is formed from nicotinamide (a product of NAD degradation) through two enzymatic steps (Katoh et al, 2006;Wang and Pichersky, 2007). Specifically, nicotinamide is hydrolyzed to nicotinate by nicotinamidase and is converted to NaMN by nicotinate phosphoribosyltransferase (NaPRTase; Wang and Pichersky, 2007;Hashida et al, 2009).…”
mentioning
confidence: 99%